ANALISA KEPUASAN PEMBELAJARAN DARING MAHASISWA STMIK SINAR NUSANTARA SURAKARTA DI MASA PANDEMI COVID-19 - Ari Wibowo; Bambang Satrio Nugroho (JURNAL ILMIAH EDUNOMIKA, 2022)
The learning process during the COVID-19 pandemic is carried out online, students and lecturers carry out lecture activities at their respective homes. Online learning can be carried out using hardware devices (laptops, smartphones, internet) and application software (google classroom, google meet). With both students interacting in online lectures with lecturers, but from some information/news we get that students prefer to study offline rather than online. This study aims to determine student satisfaction in online learning seen from the components of hardware, software and lecturer involvement. The result is that the variable of lecturer involvement has a significant and positive effect on student satisfaction in online learning with a path coefficient value (β) = 0.565. SmartPLS also produces a determination coefficient value of 39%. Exogenous variables affect endogenous variables.